1941
DOI: 10.1063/1.1750977
|View full text |Cite
|
Sign up to set email alerts
|

The Thickness of the Rigid Water Film at a Quartz-Water Interface from a Measurement of Newton's Rings

Abstract: The thickness of the water film between a quartz lens and disk was determined by measuring the radii of successive Newton's rings. The squares of these radii are a linear function of the order of the rings from the center, the intercept of the extrapolated graph of which is a function only of the radius of curvature of the lens and the vertical separation of the lens and plate. By comparing intercepts obtained from data taken before and after evaporation of a water layer, a value of the order of 100A was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1942
1942
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Derjaguin [18] has shown that thin films of water possess definite and measurable shear moduli and yield points. A further confirmation of the rigid properties of thin films of water has r ecently been reported by Eversole and Lahr [19]. An explanation of this property of the film supposes the existence of long chains of oriented water molecules extending from the solid surfaces into the interior of the liquid.…”
Section: Changes In Friction At the Start Of Slidesupporting
confidence: 52%
“…Derjaguin [18] has shown that thin films of water possess definite and measurable shear moduli and yield points. A further confirmation of the rigid properties of thin films of water has r ecently been reported by Eversole and Lahr [19]. An explanation of this property of the film supposes the existence of long chains of oriented water molecules extending from the solid surfaces into the interior of the liquid.…”
Section: Changes In Friction At the Start Of Slidesupporting
confidence: 52%
“…Derjaguin [13] found a rigidity in the water film up to 150 Å, which was confirmed by Macauley [12]. On the basis of the measurements of Newton's rings Eversole and Lahr [14] stated that water adsorbs on quartz in a rigid multilayer the minimum thickness of which is of the order of 100 Å. From Fowkes' calculations [17], it appears that about 10 statistical monolayers of water on a quartz surface still have only slightly different properties from those in the volume phase.…”
Section: Introductionmentioning
confidence: 55%
“…Because of these interactions a rigid water film is formed on quartz surface. In the literature [12][13][14][15][16] there are different opinions about the thickness of this film. Derjaguin [13] found a rigidity in the water film up to 150 Å, which was confirmed by Macauley [12].…”
Section: Introductionmentioning
confidence: 99%
“…Newton’s rings of a spherical-cap droplet are a series of concentric-ring patterns because of the interference of the light reflected on the top and the bottom interfaces of the droplet. The number of the interference rings changes with different heights of the droplets. In order to control the pattern of the templates precisely, a digital simulation was established, and the key factors influencing the Newton’s ring pattern were analyzed systemically, such as the viscosity and density of the polymer solution, and the design of the silicon pillars. Using the polymer-coated rigid templates, various ring-patterned perovskite single crystals were fabricated, which showed very fast photoluminescence (PL) characteristics on changing the design of the silicon pillars and the parameters of the fabrication process or different selections of the coating polymer solution.…”
Section: Introductionmentioning
confidence: 99%